2000
DOI: 10.1159/000045711
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus Worsens Intrarenal Hemodynamic Abnormalities in Nondialyzed Patients with Chronic Renal Failure

Abstract: Duplex Doppler sonography has been reported to be useful in examining the intrarenal hemodynamic abnormalities in various renal diseases. We investigated the impact of diabetes on intrarenal hemodynamics in patients with chronic renal failure (CRF). The resistive index and pulsatility index of the renal interlobar arteries were measured using duplex Doppler sonography in 90 CRF patients (serum creatinine >130 and <800 mmol/l, mean age 59 ± 11 years). Forty-eight patients had type 2 diabetes and 42 did not. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
5
25
1
Order By: Relevance
“…RI was determined as follows: the peak systolic velocity minus the end diastolic velocity divided by the peak systolic velocity. The usefulness of RI as a noninvasive hemodynamic assessment of the transplanted kidney was previously pointed out (7)(8)(9)(10). Our technique for CDU to evaluate RI is reproducible (coefficient of variation [CV], 3-5%) and precise.…”
Section: Clinical Follow-upmentioning
confidence: 91%
See 3 more Smart Citations
“…RI was determined as follows: the peak systolic velocity minus the end diastolic velocity divided by the peak systolic velocity. The usefulness of RI as a noninvasive hemodynamic assessment of the transplanted kidney was previously pointed out (7)(8)(9)(10). Our technique for CDU to evaluate RI is reproducible (coefficient of variation [CV], 3-5%) and precise.…”
Section: Clinical Follow-upmentioning
confidence: 91%
“…Kidney graft cumulative survival Cumulative survival of renal allografts was estimated in the different groups of transplant patients by the need for dialysis treatment, as previously described (10). Kidney graft survival was evaluated at the time of hospital discharge, according to the quartile values of the most important parameters (RI, UAE, and creatinine levels).…”
Section: Clinical Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Interstitial accumulation of advanced-glycated end products, which include collagen, elastin, and other connective tissue proteins, may be responsible for alterations of the diastolic properties of the heart in persons with hyperglycemia (30,31). On the other hand, glomerular dysfunction, intrarenal arteriosclerosis, interstitial fibrosis, and interstitial edema are related to the alteration in intrarenal hemodynamics in diabetic patients (32)(33)(34)(35)(36). Furthermore, many studies have reported that hyperinsulinemia and insulin resistance may contribute to both LV diastolic dysfunction (37)(38)(39) and glomerular hyperten- , diastolic-to-systolic ratio; RI, resistance index; A/E, peak velocity ratio of the atrial filling wave-to-early diastolic filling wave; DcT, deceleration time of the E wave; GT, glucose tolerance.…”
Section: Fig 1 Correlation Between Renal Doppler Parameters (D/s Anmentioning
confidence: 99%